A parusia de Cristo segundo Paulo: um estudo exegético-teológico de 1Ts 4,13-18 - Paganotto, Diones Rafael (2015)
The parousia of Christ is a biblical and systematic data, which attests the second coming of Christ in the end times. This research aims to examine the eschatological description of the Parousia in the First Letter to the Thessalonians, specifically in the perícope from 1 Thessalonians 4.13-18. The presentation of eschatological basis of Paul s thought, before their encounter with the Risen Christ near Damascus, prepares the literary and theological analysis of the pericope, because the Pauline message is directed to a concerned community about the fate of the deads and in doubt about the course of events in the parousia. The resurrection of Christ is closely linked to his parousia, which is, according to Paul, the reason of Christian hope and the certainty of faith that illuminates the present and the future of every Christian